Nurses Thoughts on Using Drugs Database Created by Clinical Pharmacist as Help Tool for Preparation and Administration of Drugs - Kovačević, Tijana; Dragić, Saša; Momčičević, Danica; Zlojutro, Biljana; Jandrić, Milka; Kovačević, Peđa (Scripta Medica, 2024)
Background/Aim: Intravenous therapy is a complex process usually requiring the preparation of the medicine before administration to the patient and it is well known that errors in preparation and administration can cause harm to patient. Systems that use information technology are key components of strategies to prevent medication errors in developed countries. Therefore, aim of study was to investigate nurses’ perspective on medicines database in clinical information system implemented in university hospital. Methods: A convenience sample of 79 nurses at the bedside from four different hospital wards in the 1200-bed university hospital were asked to participate in the study. The questionnaire included twenty-three questions organised in three different sections and it assessed 3 components of the medicines usage: (1) medicines preparation; (2) medicines administration; (3) clinical information system use. Mean scores were calculated for the 4- item Likert-type scales. Results: Most nurses found information in drug database reliable (Likert scale mean = 1.42 ± 0.778) and believed that using medicines database can decrease drug preparation and drug administration errors (mean: 1.35 ± 0.717) with no significant difference in mean between four different wards. Similarly, most nurses were familiar with the drug database in clinical information system (mean: 1.22 ± 0.613). Conclusion: Pharmacist as a drug expert could introduce medicines database to nurses, train them how to use it in everyday practice and explain how using information technologies can help in decreasing medication errors which leads to increasing patients’ safety during hospitalisation.